PROBIOTIC INTERVENTIONS IN GASTROINTESTINAL PHYSIOLOGY AND PATHOPHYSIOLOGY: A SYSTEMATIC REVIEW OF MODERN THERAPEUTIC FRAMEWORKS AND FUTURE INNOVATIONS - Potempa, Aleksandra; Prorok, Liwia; Oszczypała, Aleksandra; Petkow, Michał; Lipska, Katarzyna; Szyszkowska, Monika; Strojek, Zuzanna; Ustaszewska, Aleksandra; Parol, Zofia; Żyła, Mateusz (International Journal of Innovative Technologies in Social Science, 2026)
The human gastrointestinal tract is a vast and dynamic system where interactions between host cells and microbial populations regulate the condition of systemic health. Probiotics, defined as live microorganisms that administered in sufficient amounts provide a health benefit to the host, have progressed from conventional dietary supplements to advanced biotherapeutic treatments. This systematic review presents a comprehensive analysis of the physiological and pathophysiological roles of probiotics focusing on developments between 2013 and 2026. Probiotics enhance the intestinal barrier by modulating tight junction proteins, competitively excluding enteric pathogens and orchestrating immune responses via dendritic cell and regulatory T-cell pathways. Clinical data collected from recent umbrella meta-analyses shows considerable effectiveness at reducing the risk of antibiotic-associated diarrhea, managing symptoms of irritable bowel syndrome in a strain specific manner and leading to remission in ulcerative colitis. This review addresses the increase in usage of next-generation probiotics, such as Akkermansia muciniphila, and the role of genetically engineered bacteria in the targeted delivery of anti-inflammatory agents and reactive oxygen species scavengers. Additionally, the transition toward personalized medicine is discussed through the combination of multi-omics and artificial intelligence allowing to predict probiotic responsiveness in individuals. Despite recent progress, the field faces serious challenges in terms of harmonizing regulations and standardizing safety measures in vulnerable populations. This review aims to summarize current knowledge on probiotic interventions while identifying the critical knowledge gaps that need to be addressed in order to advance the next era of precision microbiome-based therapies.